IMPROVING STUDENTS’ INFERENCE SKILL IN NARRATIVE TEXT BY USING RECIPROCAL TEACHING TECHNIQUE - Hidayat, Taufiq; Sutapa Y, Y Gatot; Novita, Dewi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
Abstract: The aim of this research is to improve students’ reading inference skills of narrative text. This research was conducted to tenth year students of SMA Negeri 8 Pontianak in academic year 2013/2014. In this research, the Subject is class X IPS 3 that consists of 32 students. The researcher conducted a classroom action research in his research and acted as the teacher during the research period. The data were collected by using quantitative and qualitative method. The observation checklist table, field notes and video recorder were used as the tools of data collecting. Reciprocal Teaching Technique was used as the technique in this research which is conducted the research in two cycles. The research findings showed that the mean score of students’ reading comprehension test in the first cycle is 64.6, and in the second cycle is 77.18 which means it successfully passed the Kriteria Ketuntasan Minimum (KKM) in this school that was 65. In the first cycle, the students were able to gain the implied cause-effect. In the second cycle, the students could predict the outcome, and draw conclusions. Reciprocal Teaching Technique managed to improve the students’ reading inference skills in narrative text. This technique helped the students in understanding what the author meant and in drawing the conclusion from the narrative text given to them. Keywords: Inference skills, Reciprocal Teaching technique, Narrative Text Abstrak : Penelitian ini bertujuan untuk meningkatkan kemampuan memahami makna tersirat siswa pada teks bacaan naratif. Penelitian ini telah dilakukan terhadap siswa kelas 10 SMA Negeri 10 Pontianak pada tahun akademik 2013/2014. Dalam penelitian ini sasaran penelitiannya adalah siswa kelas X IPS 3 yang terdiri dari 32 siswa. peneliti menggunakan penelitian tindakan kelas dan berperan sebagai guru selama masa penelitian berlangsung. Data dikumpulkan dengan menggunakan tehnik kualitatif dan kuantitatif dengan menggunakan table pemeriksaan penelitian, catatan lapangan, dan rekaman video sebagai alat untuk mengumpulkan data.. Tehnik yang digunakan adalah reciprocal teaching technique dan dilaksanakan dalam 2 siklus. Hasil penelitian menunjukan skor rata-rata tes pemahaman bacaan siswa pada siklus pertama adalah 64,66, dan pada siklus kedua sebesar 77,18 yang berarti berhasil lulus terhadap nilai Kriteria Ketuntasan Minimum (KKM) di sekolah itu yaitu 65. Pada siklus pertama para siswa sudah biasa memahami tentang penyebab-akibat yang tersirat. Pada siklus kedua siswadapat memprediksi hasil dan menarik kesimpulan. Recprocal teaching technique bertujuan untuk meningkatkan kemampuan memahami bacaan siswa terhadap teks naratif. Tehnik ini membantu siswa dalam memahami maksud dan tujuan dari penulis serta membuat kesimpulan dari teks naratif yang diberikan. Kata Kunci : Pemahaman Bacaan yang Tersirat, Reciprocal Teaching technique, Teks Naratif.